A review of novel analytical diagnostics for liquid biopsies: spectroscopic and spectrometric serum profiling of primary and secondary brain tumors. Issue 9 (29th June 2016) - Spalding, Katie; Board, Ruth; Dawson, Timothy; Jenkinson, Michael D.; Baker, Matthew J.
Abstract: Introduction: Spectroscopic and spectrometric analysis of biological samples is regarded as quick, cost effective, easy to operate, and spectroscopic sample preparation involves minimal sample preparation. Results: Techniques like infrared (IR) spectroscopy, surface‐enhanced laser desorption/ionization (SELDI)‐mass spectroscopy (MS), and matrix‐assisted laser desorption/ionization (MALDI) ‐MS could enable early diagnosis of cancer, disease monitoring, and assessment of treatment responses allowing refinement, if required. Discussion: Carrying out analytical testing within outpatient clinics would dramatically cut the time spent by patients attending different appointments, at different locations, save hospital time and resources but importantly would theoretically enable a reduction in mortality and morbidity. While the advantages of such a prospect seem obvious, this review aims to evaluate the use of human serum spectroscopic and spectrometric analysis as a diagnostic tool for brain cancers, creating a platform for the future of cancer diagnostics. Abstract : Schematic showing the process for serum profiling via FTIR.